Effect of High Dose Ginger on Plasma Testosterone and Leutinising Hormone Levels in Male Rats after Lead Induced Toxicity - Fatima Riaz, Kirn-e-Muneera, Muhammad Adnan Saeed (Journal of Rawalpindi Medical College, 2017)
To study the effect of high dose ginger on plasma testosterone and leutinising hormone levels in male rats after lead induced toxicity Methods: In this quasi experimental study, 30 adult male Sprague Dawley rats were divided in two equal groups. Group A was given 0.3% lead acetate in drinking water and kept as lead control while the Group B was given a dose of 1.5gm/kg body weight ginger orally along with 0.3% lead for 42 consecutive days. Rats were then sacrificed and serum testosterone and LH levels were analyzed using ELISA technique. Data was expressed as mean±SD. P-values <0.05 were considered as statistically significant. Results: At the end of 42 days, mean serum testosterone level in Group A (control Group) was 2.2667± 0.45617ng/ml as compared to Group B (Experimental Group) 2.2667 ± 0.45617ng/ml and showed statistically insignificant change(p>0.05). Comparison of mean serum LH levels in Group A (5.3200 ± 0.72526ng/ml)revealed statistically insignificant difference (p>0.05) as compared to Group B (5.7467 ± 0.70190ng/ml). Conclusion: High dose ginger (>1gm/kg body weight) failed to enhance the suppressed testosterone level due to lead toxicity in male rats